2019
DOI: 10.1248/cpb.c18-00502
|View full text |Cite
|
Sign up to set email alerts
|

Bitterness-Masking Effects of Different Beverages on Zopiclone and Eszopiclone Tablets

Abstract: The purpose of the study was to evaluate the ability of different beverages to mask the bitterness of zopiclone and eszopiclone in tablet formulations using the artificial taste sensor and human gustatory sensation testing. The beverages tested for bitterness-masking effects were: Mugicha, Sports beverage, Lactic acid drink, Orange juice and a diluted simple syrup (an 8.5% sucrose solution). The bitterness intensities estimated by the taste sensor of zopiclone or eszopiclone one-tablet solutions mixed with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 29 publications
(29 reference statements)
1
11
0
Order By: Relevance
“…BEN and AMB, basic bitter drugs, are adsorbed on the negatively charged and hydrophobic part of the taste sensor membrane and cause a change in membrane potential by altering the charge density of the taste sensor output. In previous studies, we have demonstrated a taste-masking effect when a basic bitter drug is combined with an acidic compound, for example, diphenhydramine hydrochloride as basic bitter drug with chlorogenic acid as acidic compound [11] or zopiclone as basic bitter drug with citric acid as acidic compound [37]. In this study, 1 H-NMR analysis suggested an electrostatic interaction between the amino group of the basic bitter drug and the carboxyl group of the acidic compound.…”
Section: H-nmr Spectroscopic Analysis Of the Interaction Between Fosupporting
confidence: 50%
“…BEN and AMB, basic bitter drugs, are adsorbed on the negatively charged and hydrophobic part of the taste sensor membrane and cause a change in membrane potential by altering the charge density of the taste sensor output. In previous studies, we have demonstrated a taste-masking effect when a basic bitter drug is combined with an acidic compound, for example, diphenhydramine hydrochloride as basic bitter drug with chlorogenic acid as acidic compound [11] or zopiclone as basic bitter drug with citric acid as acidic compound [37]. In this study, 1 H-NMR analysis suggested an electrostatic interaction between the amino group of the basic bitter drug and the carboxyl group of the acidic compound.…”
Section: H-nmr Spectroscopic Analysis Of the Interaction Between Fosupporting
confidence: 50%
“…In those articles, drug ratios were set 1:0.5, 1, 2 [15] or 1:1, 2, 8. [16] Whereas the drug ratios employed for taste sensor and human gustatory sensation test (AML:VAL; 1:7.7-30.7) were differed from those employed for 1 H-NMR spectroscopic analysis, the signal shifts of specified proton in AML would be occurred under our experimental conditions in theory because the signal shifts of specified proton in AML were expected to be occurred VAL dose dependently. In the 1 H-NMR spectrum of AML with VAL (AML:VAL = 1:1, 2 or 4), the signal of AML protons 23 and 24 was shifted downfield in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 88%
“…The experimental protocol of this study (No. [14][15][16][17][18][19][20] was approved on 20 May 2014, by the ethical committee of Mukogawa Women's University.…”
Section: Human Gustatory Sensation Testmentioning
confidence: 99%
“…It is estimated that bitter substance establishes electrostatic interactions and hydrophobic interaction with bitter taste receptor by docking simulation of bitter taste receptor with bitter substance. 34) AML which is a basic bitter drug, has an amino group which is positively charged and hydrophobic group in the structure. Electrostatic interaction and hydrophobic interaction which are formed in AML with bitter taste receptor on the mucous membrane in the oral cavity are expected to be main mechanism of bitterness caused by AML.…”
Section: H-nmr Spectroscopic Analysis Of the Interaction Between Aml mentioning
confidence: 99%